2013
DOI: 10.1038/sj.bdj.2013.876
|View full text |Cite
|
Sign up to set email alerts
|

Oral surgery: part 2. Endodontic surgery

Abstract: In the past, the interaction between dentoalveolar surgery and restorative dentistry has been limited to the removal of teeth with pulp and/or periradicular disease or those that were unrestorable. However, with the increasing dental awareness of the population and the retention of teeth into later life, the interaction between dentoalveolar surgery and restorative dentistry is becoming a fundamental aspect of clinical practice. Indeed, endodontic and implant surgery are core activities that facilitate the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…( 9 ) in which they found that lesions ≤ 10 mm had an 80% of success rate while the larger ones showed a success rate of 53% after a period from 4 to 10 years. A favorable prognosis of periapical surgery seems almost assured when the periapical lesion is less than 5 mm ( 5 , 7 , 12 - 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…( 9 ) in which they found that lesions ≤ 10 mm had an 80% of success rate while the larger ones showed a success rate of 53% after a period from 4 to 10 years. A favorable prognosis of periapical surgery seems almost assured when the periapical lesion is less than 5 mm ( 5 , 7 , 12 - 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relation between prognosis and type of tooth is not clear yet. Many authors agree that incisors and canines have higher success rates in endodontic surgery ( 5 - 7 , 9 , 12 , 14 , 15 ). This may be explained because the anterior sectors are more accessible and permit an excellent view of the operative field, thus obtaining a better apical seal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, cuando no existe una adecuada relación corona-raíz el corte del ápice puede llegar a comprometer la estabilidad del diente dentro de su alvéolo, por lo que el conservar la longitud total del órgano dentario es un objetivo a alcanzar 14 . Con la utilización de puntas de ultrasonido se logra preparar una cavidad apical estrecha, larga, de paredes paralelas, sacrificando poco tejido dentario, disminuyendo el riesgo de perforaciones radiculares y facilitando la colocación del material retrógrado, este material de obturación debe tener la capacidad de sellar a las bacterias y sus productos dentro del conducto radicular impidiendo su salida hacia los tejidos periapicales y permitiendo la regeneración de los tejidos 15 .…”
Section: Introductionunclassified